LEGAL PROTECTION OF HOLDERS MINORITY SHARES REVIEWED FROM ASPECT EASE OF DOING BUSINESS - Priyogo, Kukuh (Inspiring Law Journal, 2024)
Generally, minority shareholders do not have great access to immediate information about the company in which they invest their capital. The purpose of this research is to determine the legal regulations for legal protection for minority investors according to Law Number 40 of 2007 concerning Limited Liability Companies and Ease of Doing Business (EODB), forms of investment crime involving minority shareholders and legal protection for minority shareholders if their rights are violated in a civil manner. The type and research approach used is normative juridical legal research with a case study approach and descriptive research nature, which uses Islamic legal data and secondary data as well as supporting interview data to strengthen the researcher's case study. Then, the data is processed using qualitative analysis. Based on the results of the research, first, the legal regulation of legal protection for minority investors according to Law Number 40 of 2007 concerning Limited Liability Companies regulates the authority of shareholders in filing a lawsuit against the company if they are harmed. There are at least 5 (five) authorities in demanding the rights of minority shareholders. that can be done. Second, the legal factors that minority shareholders do not fulfill are that many minority shareholders do not know about their rights in a Limited Liability Company. there is consumer ignorance and asymmetric information, minority shareholders do not want to file lawsuits and there is lack of clarity in the field and orientation of implementing the protection of minority shareholder rights. Third, legal protection for minority shareholders if their rights are violated in a civil manner, namely that minority shareholders are given the opportunity to file 2 (two) types of lawsuits, namely a direct lawsuit and a derivative lawsuit